Novel Therapy for Acquired Tracheomalacia with a Tissue-Engineered Extraluminal Tracheal Splint and Autologous Mesenchymal-Derived Chondrocytes - Melgarejo-Ramírez, Yaaziel; Ceballos-Cantú, Juan C.; Montes-Olave, Eric de J.; Hernández-Tapia, Bruno; Rojas-Figueroa, Víctor; Ramírez-Arroyo, Gabriela; Cortés-Acosta, Fabiana; Dorantes-Pavón, Mario; Lecona-Butrón, Hugo; Beltrán-Rodríguez-Cabo, Olga E. (International Archives of Otorhinolaryngology, 2022)
Introduction Acquired tracheomalacia (ATM) is characterized by a loss of structural strength of the tracheal framework, resulting in airway collapse during breathing. Near half of the patients undergoing prolonged invasive mechanical ventilation will suffer tracheal lesions. Treatment for ATM includes external splinting with rib grafts, prosthetic materials, and tracheal resection. Failure in the use of prosthetic materials has made reconsidering natural origin scaffolds and tissue engineering as a suitable alternative.Objective To restore adequate airway patency in an ovine model with surgically-induced ATM employing a tissue-engineered extraluminal tracheal splint (TE-ETS).Methods In the present prospective pilot study, tracheal rings were partially resected to induce airway collapse in 16 Suffolk sheep (Ovis aries). The TE-ETS was developed with autologous mesenchymal-derived chondrocytes and allogenic decellularized tracheal segments and was implanted above debilitated tracheal rings. The animals were followed-up at 8, 12, and 16 weeks and at 1-year postinsertion. Flexible tracheoscopies were performed at each stage. After sacrifice, a histopathological study of the trachea and the splint were performed.Results The TE-ETS prevented airway collapse for 16 weeks and up to 1-year postinsertion. Tracheoscopies revealed a noncollapsing airway during inspiration. Histopathological analyses showed the organization of mesenchymal-derived chondrocytes in lacunae, the proliferation of blood vessels, and recovery of epithelial tissue subjacent to the splint. Splints without autologous cells did not prevent airway collapse.Conclusion It is possible to treat acquired tracheomalacia with TE-ETS without further surgical removal since it undergoes physiological degradation. The present study supports the development of tissue-engineered tracheal substitutes for airway disease.
Keywords: airway splint; tracheomalacia; tissue engineering; respiratory disorder; extraluminal splint; prostheses and implants